Effectiveness of Laser Hemorrhoidoplasty in the Treatment of Hemorrhoidal Disease in Western Nepal: A Ambispective Descriptive study - Timilsina, Bishow Deep; Timilsina, Babita Subedi (Nepal Journal of Medical Sciences, 2026)
Introduction: Hemorrhoidal disease is a common anorectal condition causing pain, bleeding, and discomfort. Conventional hemorrhoidectomy, although effective, is associated with significant postoperative pain and delayed recovery. Laser hemorrhoidoplasty (LHP) has emerged as a minimally invasive alternative that aims to reduce morbidity while ensuring effective treatment. This study evaluated the short- and long-term effectiveness of LHP in patients with Grade II-IV hemorrhoids. Methods: A total of 96 patients who underwent LHP at Manipal College of Medical Sciences (MCOMS), Pokhara between 1st July 2023 to 30th June 2024 were included in the study following ethical approval from institutional review board of MCOMS using convenience sampling. Retrospective data were obtained from hospital records, while prospective follow-up involved verbal and written informed consent. Long-term outcomes, including bleeding, recurrence, incontinence, anal stenosis, perianal fistula, and fissure, were assessed via follow-up and medical records. Results: Of 96 patients, 65 (67.7%) were male and 31 (32.3%) were female. Grade III hemorrhoids were most common (61.5%), followed by Grade II (25.0%) and Grade IV (13.5%). Mean operative duration was 19.72 ± 3.19 minutes with minimal blood loss 9.8 ± 3.4 ml. Postoperative bleeding and submucosal edema were more frequent in higher-grade hemorrhoids (p<0.001). Conclusions: LHP is a safe and effective minimally invasive treatment for symptomatic hemorrhoids, providing rapid pain relief, minimal intraoperative blood loss, and quick return to daily activities. While short- and long-term outcomes are favorable for Grade II and III hemorrhoids, Grade IV patients require closer monitoring due to higher complication rates